Enduring phenotype of episodic status migrainosus in a prospectively identified patient. (19th December 2018) - Smith, Jonathan H
Episodic status migrainosus is a previously described migraine variant where the exclusive phenotype is that of relapsing status migrainosus. The majority of cases have been reported based on retrospective chart review. A prospectively identified case fulfilling previously published criteria for episodic status migrainosus is reported, with an enduring pattern of attacks meeting criteria for status migrainosus over a 35-year period. A family history in a maternal aunt of a similar phenotype was noted. This prospectively identified case further validates the existence of episodic status migrainosus as a novel nosologic entity. The family history in our case suggests the possibility of genetic susceptibility. Perspective regarding a potential temporal continuum between acute migraine, status migrainosus, and new daily persistent headache is described. Status migrainosus may occur both as a complication of migraine and in the pure form of episodic status migrainosus.